Faktor-faktor yang Mendukung dan Menghambat Dilakukannya Versi Luar pada Kehamilan dengan Presentasi Bokong di Yogyakarta - I Made Pariartha; Rukmono Siswishanto; Nuring Pangastuti (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: Guidelines recommend that external cephalic version (ECV) should be offer to all women with fetus in breech presentation at term. Many literature show external cephalic version can lowering c-section rate caused by breech presentation.Objective: To explore the determinants (barriers and facilitators) affecting obstetricians and gynaecologists to do external cephalic version at Yogyakarta.Method: Explanatory mixed methods design with quantitative-qualitative model. Survey with validated questionnaire and in-depth interview with semi-structured question was done January 2019 until August 2019.Results and Discussion: 72 respondents (83.7%) was responded to questionnaire and in-depth interview was done to 12 respondents. Adherence to ECV guideline was varied: counselling (20.8%), advising for ECV (15.3%), and arranged for ECV to for (almost) all their clients (16.6%). Although 76.4% of respondents considered ECV to be an effective treatment for preventing caesarean childbirth, only 18.1% respondents agreed that every client with breech presentation should undergo ECV. Self-efficacy was the most important determinant influencing adherence. In-depth interview shows several determinants to performed or did not performed ECV: skill of clinicians, guideline for ECV, facility to emergency c-section, ECV characteristic, cost, other methods for breech presentation, perception about ECV in lowering c-section rate, perceived ECV risk and patient preferences.Conclusion: Most respondents agreed that ECV was effective intervention to reduce caesarean childbirth, but adherence to counselling, advising and arranging ECV for clients still very low. Several determinants influenced obstetrician and gynaecologists to perform or did not perform ECV.Keywords: External cephalic version; breech presentation; determinants.